2004
DOI: 10.1158/0008-5472.can-03-2538
|View full text |Cite
|
Sign up to set email alerts
|

Induction of Adipophilin-Specific Cytotoxic T Lymphocytes Using a Novel HLA-A2-Binding Peptide That Mediates Tumor Cell Lysis

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
1

Year Published

2004
2004
2013
2013

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(35 citation statements)
references
References 19 publications
1
33
1
Order By: Relevance
“…ADFP, C-MET, and RSG-5 are not immunogenic in patients with ccRCC, as we did not detect T-cell responses specific for these antigens, despite their frequent overexpression. This finding is in agreement with previously published data on rare T-cell responses in patients with ccRCC (15), even though ADFP-and C-MET-specific T cells could be expanded from the blood of healthy donors (33,34). RGS-5 overexpression did not result in detectable RGS-5-specific T-cell responses in our cohort, although such responses were reported in the blood of healthy donors and patients with acute myeloid leukemia (42).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…ADFP, C-MET, and RSG-5 are not immunogenic in patients with ccRCC, as we did not detect T-cell responses specific for these antigens, despite their frequent overexpression. This finding is in agreement with previously published data on rare T-cell responses in patients with ccRCC (15), even though ADFP-and C-MET-specific T cells could be expanded from the blood of healthy donors (33,34). RGS-5 overexpression did not result in detectable RGS-5-specific T-cell responses in our cohort, although such responses were reported in the blood of healthy donors and patients with acute myeloid leukemia (42).…”
Section: Discussionsupporting
confidence: 93%
“…In addition to CA-IX, ADFP, Cyclin D1, C-MET, and RGS-5 are also overexpressed in ccRCC (14). In contrast to published reports (33,34), we found that ADFP expressed more frequently (65%) than C-MET (30%). Cyclin D1 is a cell-cycle regulator crucial for the G 1 -S transition (35) and is overexpressed in many cancers including colorectal and breast carcinoma (36,37).…”
Section: Discussioncontrasting
confidence: 93%
“…This approach discloses the complex nature of cancer cells and leads to identification of genes of which expression patterns are different in tumors when compared with the patterns in nontransformed cells (19). Because TAAs should theoretically be expressed excessively and preferentially by the tumor cells but not by the normal tissues, gene expression profiling with cDNA microarray technologies is useful to identify TAAs (20,21). We analyzed the expression profiles of the newly identified genes with a genome-wide cDNA microarray technology, selected TAA candidates from these genes with the information, and examined whether they contain antigenic T-cell epitope peptides to prove that they are indeed TAAs.…”
Section: It Has Been Demonstrated That Cd8mentioning
confidence: 99%
“…In this report, the peptide vaccine elicited cytotoxic immunity against a variety of cancer cells expressing endogenous adipophilin such as renal cell carcinoma, breast cancer, melanoma, and multiple myeloma etc. [73]. However it remained obscure whether the induced cytotoxic immunity targeted the adipocyte as well, or whether the immunity contributed the antitumor effects if this was the case.…”
Section: Other Vaccines Targeting Cancer Microenvironmentmentioning
confidence: 99%